Opening the Black Box of Tax Reforms in Latin America (Global Journal of Human-Social Science, 2023)
This article verifies how the types of tax reform are related to income and how they are distributed over time and by jurisdiction The analysis focused on the tax reforms that took place in Latin America between 1990 and 2004 The data came from a survey carried out by the Inter-American Development Bank IDB in 2006 A greater reform impetus was observed in the early 1990s accompanying the re-democratization of the countries of the region The most reformed taxes were value added tax and income tax The countries that reformed the most were Argentina Colombia Costa Rica and Guatemala while Bolivia Chile Dominican Republic Panama and Paraguay had a more conservative profile The study contributes to the formulation of tax policy and to academic research based on legislative changes and typology of tax reforms
Keywords: tax; tax reform; fiscal policy; income tax; value added tax